2012
DOI: 10.1111/j.1365-2648.2012.06016.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between fatigue and Internet addiction in female hospital nurses

Abstract: Nurses should pay attention to their Internet activity and whether it adds to their fatigue levels. Addictive behaviour should promptly be dealt with to ensure that the best care is provided to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 54 publications
0
31
0
2
Order By: Relevance
“…Previous research has also established that computer screen lights can have negative effect on circadian rhythm and lead to sleep phase delay [Petit et al 2016]. Similarly, IA plays an important role in daytime sleepiness and sleeping disorders [Ferreira et al 2017] and fatigue [Lin et al 2013]. Other study has also reported that IA has negative impacts on sleep including sleep deprivation and fatigue [Bener et al 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also established that computer screen lights can have negative effect on circadian rhythm and lead to sleep phase delay [Petit et al 2016]. Similarly, IA plays an important role in daytime sleepiness and sleeping disorders [Ferreira et al 2017] and fatigue [Lin et al 2013]. Other study has also reported that IA has negative impacts on sleep including sleep deprivation and fatigue [Bener et al 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Compulsive internet behavior has been considered as one of the most relevant dimensions of internet addiction (Lortie and Guitton, 2013), with past studies using both internet addiction and compulsive Internet use to refer to the same phenomenon (Lin et al, 2013). Previous research has demonstrated that addiction can be generated not only to internet usage, in general, but also towards specific SNS sites, with compulsion being one of its underlying components (De Cock et al, 2014;Kang et al, 2013).…”
Section: The Mediating Role Of Social Networking Sites Addictionmentioning
confidence: 99%
“…The notion of an IAD is based on observations that some individuals display signs of problematic internetrelated behaviors similar to those observed for other behavioral addictions, such as gambling (Block, 2008;Young, 1998). In particular, excessive use of the internet has been shown to produce severe disruption to the affected individual's everyday functioning, especially in terms of their social and work commitment (Bozoglan, Demirer, & Sahin, 2013;Lin, Tsai, Chen, Koo, 2013;Shaw & Black, 2008).…”
mentioning
confidence: 99%